Eksplorasi Nilai-Nilai Tradisi Ramayana dalam Arsitektur Pura Desa Batuan Gianyar (Tinjauan Konsep Satyam Sivam Sundaram) - Putra, Cokorda; Cahaya Wardani, A. A. A. Made (Jayapangus Press, 2024)
One example of the wealth possessed is depicted in the Ramayana story, which has long been ingrained in Balinese culture. The Ramayana story is often expressed in various forms, including Bali's distinctive carvings. This study aims to detail and analyze the extent to which the values of the Ramayana tradition are reflected in the sculptures and reliefs at Pura Desa Batuan, Gianyar, with a specific focus on the concept of Satyam Sivam Sundaram and other traditional values. The goal is to explore the values of the Ramayana tradition through the ornaments adorning Pura Desa Batuan. This research employs a qualitative approach with a descriptive method. The guiding theory for this research is the Transforming Tradition theory. Based on the application of this theory, the researcher chooses to use the ATUMICS (Artefact-Technique-Utility-Material-Icon-Concept-Shape) method to explain the ornaments on the research objects. Data collection techniques include participatory observation, direct observation, and involvement in the research site. The object of study is Pura Desa Batuan in Gianyar, Bali. The research findings indicate that both carvings and reliefs as ornaments have direct and indirect influences on architecture and are capable of illustrating the concept of Satyam Sivam Sundaram, which refers to truth, purity, and beauty. Moreover, the Ramayana Tradition reliefs provide an image and contribute to the essence and spirit of the Pura Desa Batuan building. Furthermore, the Ramayana Tradition reliefs also emit a vibration of sanctity for the Pura Desa Batuan building in Gianyar. The values of sincerity, purity, and beauty are reflected in every element of the building, creating a sacred atmosphere that provides a spiritual experience for Hindu worshippers and visitors alike. Through the emission of vibrations and the preservation of the Ramayana heritage, Pura Desa Batuan stands as living proof of the richness and perpetuity of tradition.